Teknik Terjemahan Sebagai Padanan Makna Tindak Tutur Tidak Langsung Literal Dalam Novel Another Karya Ayatsuji Yukito - Faradila, Finanda Nur; Khasanah, Ismatul; Junining, Esti (Humanis, 2022)
This research is discussing the usage translation techniques with the purpose of understanding how match a meaning of an utterance, specifically indirect-literal utterance in a novel Another by Ayatsuji Yukito with Molina and Albir (2002) translation technique theory, supported by Baker (2011) translation equivalent theory. This research is qualitative descriptive type that used transcription method for collecting data. Based on the analysis, it is found that 13 translation technique has been used, such as amplification, reduction, borrowing, calque, compensation, established equivalence, amplification linguistic, compression linguistic, literal translation, modulation, particularization, generalization and transposition. These techniques have some functions, such as to match different formats (transposition, calque, amplification linguistic, compression linguistic, modulation), to match specific culture differences (borrowing, amplification, established equivalence), to consider the naturalness of expression in speech (transposition, calque, amplification linguistic, compression linguistic, modulation, generalization, particularization). There are also techniques that are used without any matching consideration, the technique is called literal translation.particularization). There are also techniques that are used without any matching considerstion, the technique is called literal translation.